Philippines : Staff Report for the 2004 Article IV Consultation and Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2005)
This paper examines the Philippines's 2004 Article IV Consultation and Post-Program Monitoring Discussions. GDP growth has exceeded expectations, but unemployment remains high. With exports staging a recovery and consumption boosted by overseas remittances and the election, GDP grew by 6.1 percent in 2004, up from 4.7 percent in 2003. The near-term outlook for the Philippines economy is clouded by the uncertain external environment. The rapid growth in 2004 is unlikely to be sustained, particularly given slowing global demand in the information technology sector and rising interest rates.